2018
DOI: 10.1080/13607863.2018.1488944
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive stimulation therapy for brazilian people with dementia: examination of implementation’ issues and cultural adaptation

Abstract: Objectives: The prevalence of dementia has been increasing particularly in developing countries. However, people with dementia (PwD) in Brazil are currently offered no psychosocial treatment upon diagnosis. Cognitive Stimulation Therapy (CST) that originated in the UK has proven benefits on cognition and quality of life in PwD. We investigate the possible issues for the implementation of CST for the Brazilian population and its cultural appropriateness.Method: Individual interviews and focus groups were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 14 publications
2
53
0
Order By: Relevance
“…A shortage of qualified professionals was identified here as a barrier to delivering CST and this shortage across services has also been suggested as negatively impacting on how a service user evaluates the quality of a healthcare service (28). In Brazil, it has been suggested that CST could be viewed as additional work for both caregivers and healthcare professionals (24). This is consistent with the barrier of healthcare professionals having competing demands on their time documented here.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A shortage of qualified professionals was identified here as a barrier to delivering CST and this shortage across services has also been suggested as negatively impacting on how a service user evaluates the quality of a healthcare service (28). In Brazil, it has been suggested that CST could be viewed as additional work for both caregivers and healthcare professionals (24). This is consistent with the barrier of healthcare professionals having competing demands on their time documented here.…”
Section: Discussionsupporting
confidence: 73%
“…Dispensaries serve local communities, followed by health centers, hospitals and larger referral hospitals (20). The three countries chosen for this work were part of the CST-International research programme (21) and teams in each country had previously completed the formal adaptation of CST (22)(23)(24) using the established methodology (25). As this was a stakeholder project and not a formal research study, no identifying information was collected from stakeholders beyond their job title and no formal analysis was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate CST implementation in other cultures, adaptation guidelines have been developed 17 with an approach involving stakeholders in the cultural adaptation process. A previous report by our group has described steps used for translating CST materials, also examining implementation issues and cultural adaptation 18 . The results indicate that CST is appropriate for the Brazilian population, with some minor amendment needed to address cultural issues (e.g., faces of famous Brazilian people or typical Brazilian foods).…”
Section: Introductionmentioning
confidence: 84%
“…The CST program has been described elsewhere, 12 with the intervention in the current study being implemented according to the translated and adapted procedures described by Bertrand and colleagues 18 . For the treatment group, the program was conducted by three researchers (Valeska Marinho, Iris Bomilcar and Renata Naylor), in groups with between five and eight participants.…”
Section: Methodsmentioning
confidence: 99%
“…There is, in fact, important evidence that contradicts these notions. For example, all rehabilitation and cognitive stimulation efforts (e.g., Bertrand E. et al, 2019) attest to the potential of improvement of people with dementia and other patients with amnesia (Wilson, 2009). Specifically related to awareness of difficulties, the notion of implicit awareness (Morris and Mograbi, 2013) suggests that behavioral and affective change may happen without explicit knowledge by patients.…”
Section: What Is In a Metaphor And Concluding Thoughtsmentioning
confidence: 99%